Pengaruh Inovasi Produk Terhadap Keputusan Masyarakat Menggunakan Jasa Perbankan Syariah (Studi Kasus Pada Pt Bank Muamalat Tbk Cabang Kendari) - Sakinah, Dewi Inayatul (IAIN Kendari, 2024)
The purpose of this study is to find out the influence of religious understanding,product innovation and service on people's decisions using Islamic banking services (case study at PT Bank Muamalat Tbk Kendari Branch). The type of research used in this research is quantitative research. Data collection techniques by way of questionnaires and documentation. While the data analysis techniques used are desriptive statistical analysis and inferential analysis. From the results of the study it is known that product innovation has a positive and significant effect on people's decisions to use Islamic banking services at PT Bank Muamalat Tbk Kendari Branch, with a calculated t value> t table (23,362> 1.658) with a significance level of 0.000